Understanding attitude and knowledge of nonpsychiatric postgraduate residents for mental health conditions: A comparative study - Pankaj Kumar; Cherry Sikka; Rupesh Chaudhary; Nikhil Gautam (Annals of Indian Psychiatry, 2023)
Context: Psychiatric exposure of medical and paramedical staff during training being grossly inadequate eventually leads to insufficient knowledge and misconceptions about psychiatric illnesses and their treatment. Aims: The importance of this study would be to bring into limelight the attitude of residents who will be practicing as soon as their residency finishes. Since postgraduate residents are the ones stepping into the field of medical practice, their attitude toward mental health is of extreme importance. Settings and Design: This was a cross-sectional study done at a tertiary care hospital. Materials and Methods: The sample consisted of 1st- and 3rd-year postgraduates belonging to nonpsychiatric branches (50 each), selected by random sampling. Statistical Analysis Used: A comparison of quantitative variables between the study groups was done using Student's t-test. For comparing categorical data, Chi-square test was performed and exact test was used. Results: The scoring of the Medical Condition Regard Scale, which showed the overall regard and attitude, improved as the year of residency changed with more patient exposure the attitude of the residents toward psychiatric illnesses and patients suffering from psychiatric illnesses improved. Conclusions: In the current study, we found that the PG residents have multiple lacunae in their knowledge about psychiatric patients, psychiatric illness, psychiatric treatment, psychiatrists, and subject of psychiatry. Through exposure in-depth and high-quality teaching and internship along with the emphasis on consultation-liaison will decrease the negative attitude and improve knowledge.